Pengaruh Motivasi, Kepemimpinan, Disiplin Kerja Terhadap Kinerja Karyawan CV. Kazar Teknologi Indonesia - Defisa, Tomi; Luthfiansyah, Hilmi; eka nugrahaeni, Agrisa (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to describe the problems that exist in Cv.Kazar Teknologi Indonesia where the development of the technology business sector is an opportunity for small companies for sub-sectoral work. Take advantage of opportunities to reach consumers, create competition between technology service companies. similar. This also makes every company must innovate creative marketing strategies in selling the services offered to the target audience. cv. Kazar Teknologi Indonesia, is a service company, which was founded in 2010 and is engaged in technology services. Constraints that often occur are when project work schedules are in need of leadership direction, company motivation and good work discipline between fields of work in Nekata Printing so that employee performance can be followed up as soon as possible so as not to cause disappointment from consumers